Preliminary Study on Educational User Interface Architecture for Social Network - Muniratu Salihah Aishatun bt Yahya, Siti; bt Ahmad, Suzana (International Journal of Engineering and Technology, 2018)
Social network has becoming a major platform of daily activities from leisure to business purposes.Â  Educational activities could also benefited from this trending platform for its dynamic functions. Among educational activities that could be performed on social network are collaborative studies, blended learning and group activities. Through this platform, students and teachers can be connected to each other for the purpose of exchanging ideas and information. High-end interaction and connectivity between students and teachers makes social network popular as learning platform. A preliminary study on an online tuition conducted by latihminda.com has been conducted. The focus of this study is to proposed a suitable educational user interface architecture for social network education. Elements of real-time interaction and intelligent avatar used by latihminda.com are studied and an educational user interface architecture for social network are proposed in this paper.Â Â